Our Virtual Existence: the Eternity is here! - António Jesus Monteiro de Castro (2006)
What characterizes the existence of a person? The fact that it has a blood and flesh body, the actions and goals achieved during is life, or both? Like we all have a real existence, we propose to create a virtual existence for each one of us. Like our real life, our virtual life would have knowledge of our goals and desires in all areas. Like our real life, our virtual life would have autonomy. It would know all about us, our ID number and data, our IRS information, our health information, and so on. The "real I" should be able to define the preferences and goals of the "virtual I". Those preferences and goals should be possible to change along our life. It should be able to pursue those goals in our behalf. It should be able to learn, interact and adapt to the virtual environment, like our "real I" has to learn, interact and adapt to the real environment. Our "virtual I" should exist, of course, in a virtual space: the Internet. It should seek our goals and preferences, inform and give advices to the "real I". It should be able to communicate all this to us through our home PC, our mobile phone, PDA, and so on. We should be able to carry our "virtual I", if we wish, with everything about us, in our mobile device or in a flash pen. Because it knows everything about us, it should be able to represent us in the restaurant information system, in the IRS information system, in the health information system, in the Bank information system, and so on. Say goodbye to ID cards, driving licenses, passports, and so on. Our "virtual I" will represent us to the police and immigration officer. When our "real I" dies our "virtual I" can continue to live, representing and pursuing our goals. Our family and friends can continue to talk with us, through our "virtual I". - The eternity is here!